Mapping of Socioeconomic Life of Fishermen Community in Maitara Island Tidore Kepulauan City in Maluku Utara Province - Asnita Ode Samili; Ramli Umar; Abdul Malik (Universitas Negeri Makassar, 2017)
The research aims to discover: (1) the characteristics of socioeconomic life of fishermen community in Maitara Island Tidore Kepulauan City in Maluku Utara Province, (2) the survival strategy of fishermen community in Maitara Island Tidore Kepulauan City in Maluku Utara Province. The data were analyzed by using descriptive qualitative analysis to reveal the facts about Socioeconomic Life of Fishermen Community in Maitara Island Tidore Kepulauan City in Maluku Utara Province. The samples were taken by using purposive sampling method, namely taking samples based on certain considerations by the researcher such as choosing respondents who lived in the area of Maitara Island who worked as fisherman. The data were collected by using questionnaire in form of questions, observation, interview, and documentation. The results of the research reveal that (1) the characteristics of socioeconomic life of fishermen community in Maitara Island from social perspective particularly in fishermen’s education who did not finish Primary School is 56.33 percent and the rest who finished Primary School is 30.98 percent, Junior High School is 9.85 percent and Senior High School is 2.81 percent. The aforementioned results clearly show of low education of fishermen community and from economic perspective of fishermen’s monthly income is 76.05 percent with the income range 1.500.000-2.500.000 and the rest are above 2.500.000 and even there is below 1.500.000. It is due to low quality of human resources which influence their incomes and vice versa, if their incomes are low, then it would influence the human resources, namely low education. It can be seen that they could catch lots of fish but they could not manage it well due to low quality of human resources, (2) the survival strategies of fishermen community are conducting side jobs or job diversification empowering family, namely wife and children, in market to fulfill their families’ needs.